2006
DOI: 10.1161/circulationaha.105.001594
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Bicuspid Aortic Valves in Patients With Aortic Regurgitation

Abstract: Background-Bicuspid aortic valve regurgitation can be caused by a defect in the valve itself or by dysfunction of one or more components of the aortic root complex. A successful repair thus requires correction of all aspects of the problem simultaneously. We review our experience addressing both the valve and the aortic root when correcting bicuspid valve regurgitation. Methods and Results-Between 1996 and 2004, we treated 68 patients for aortic regurgitation. Thirty patients had isolated aortic regurgitation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 17 publications
1
47
1
4
Order By: Relevance
“…16 However, satisfactory mid-term results have been reported with these techniques. [17][18][19] The similar outcomes for bicuspid and tricuspid AVs in sparing surgery reported by Shäfers and colleagues (Aicher et al 20 ) and confirmed in this series (Table 4) support the approach of bicuspid valve preservation, even when cusp repair is more frequent and complex than in the tricuspid AV.…”
Section: De Kerchove Et Al Aortic Insufficiency and Sparing Surgery S123supporting
confidence: 84%
“…16 However, satisfactory mid-term results have been reported with these techniques. [17][18][19] The similar outcomes for bicuspid and tricuspid AVs in sparing surgery reported by Shäfers and colleagues (Aicher et al 20 ) and confirmed in this series (Table 4) support the approach of bicuspid valve preservation, even when cusp repair is more frequent and complex than in the tricuspid AV.…”
Section: De Kerchove Et Al Aortic Insufficiency and Sparing Surgery S123supporting
confidence: 84%
“…8,23,24 The application of valve-preserving aortic replacement has been published using both root remodeling and valve reimplantation. 6,20,25 In the meantime, it has become evident that reconstruction of the aortic valve is associated with fewer valve-related complications than reported previously for valve replacement. 16,26 The present results principally confirm the positive early results published previously in patients with BAVs.…”
Section: Aicher Et Al Valve Configuration In Bicuspid Aortic Valvesmentioning
confidence: 98%
“…The techniques used to spare or repair the aortic valve have been described elsewhere. 2,3,16 In addition to aortic surgery, 63 patients needed an additional procedure, including mitral valve repair in 29, tricuspid valve annuloplasty in 4, coronary artery bypass graft surgery in 24, closure of an atrial septal defect in 5, and closure of a ventricular septal defect in 1.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…In recent years, however, repair techniques for diseased aortic valves have received increasing attention. [1][2][3][4][5][6][7][8][9][10] Innovations in operative techniques, an improved understanding of the functional anatomy of the aortic valve and root, as well as an increased awareness of the mechanisms leading to AR have undoubtedly contributed to this renewed interest. 11,12 Recently, we have described a functional classification of AR that addresses most of the pathological aspects of leaking aortic valves.…”
mentioning
confidence: 99%